IMPACT OF INTERNATIONAL STANDARDS ON MARITIME EDUCATION: PERSPECTIVES OF JUNIOR CADETS - Sihombing, Derma Watty; Dwiyani , Nurindah; Martha, Yayu Nopriani; Hutabarat, Christiani; Sutrisno (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) STIP Jakarta, 2024)
This research explores the impact of international standards on maritime education through the perspectives of 45 junior cadets. Utilizing qualitative methods, including interviews and observations, the study investigates the alignment of educational programs with standards set by the International Maritime Organization (IMO) and the Standards of Training, Certification, and Watchkeeping for Seafarers (STCW). Findings reveal a strong perception of alignment with international standards among participants, emphasizing the importance of consistency and global recognition in maritime education. Additionally, the analysis highlights the relevance of curriculum content to professional needs, the significance of continuous professional development, and the availability of opportunities for career advancement within educational institutions. The research contributes to discussions surrounding the optimization of maritime education and underscores the importance of lifelong learning and professionalism in preparing junior cadets for successful careers in the maritime industry.